Kedudukan Hukum Al-Sunnah dalam Al-Qurâ€™an - Al Hadi, Abu Azam (Al-Daulah: Jurnal Hukum dan Perundangan Islam, 2018)
Abstract: the legal position of al-sunnah (prophet tradition) is as the source of Islamic law. However, each has distinction in term of transmission. While all verses of the Quran were transmitted successively (tawatur), not many prophet traditions are successive. Instead, they are reported in solitary manner. Thus, further meticulous examination of its authenticity is a must. The examination involves the number of transmitters as well as their personality. Therefore, the legal position of al-sunnah vis-Ã -vis the Quran comes in three functions: Firstly, the position of al-Sunnah as source of Islamic law secondary to the Quran and functions to elaborate the general meaning of the Quran. Secondly, al-Sunnah interprets verses of the Quranâ€™ Thirdly, al-Sunnah perform as further interpretation for the Quran in term of bayÃ¢n al-mujmal, bayÃ¢n taqyÃ®d al-muthlaq, bayÃ¢n al-takhshish al-â€˜Ã¢m, dan bayÃ¢n tawdhÃ®h al-musykil. Key words: al-sunnah, the Quran, source of Islamic law